The influence of health education through video media about menarche on knowledge level of teenage students in primary school 1 paret bolaang district east mongondow - Irma M Yahya; Marry Rimporok; Hardayani Limpong (Jurnal EduHealth, 2024)
Menarche is the first menstruation experienced by women as a sign of maturity. Menarche is caused by the first release of blood from a woman's genitals, which is the shedding of the inner lining of the uterus which contains many blood vessels and menarche occurs. The aim of this research was to determine the effect of health education about menarche on the level of knowledge of female students at SD N 1 Paret, East Bolaang Mongondow Regency. The research was conducted using quantitative descriptive research methods with a cross sectional approach. Samples were taken based on the number of respondents of 15 people using total sampling. Data collection was carried out by means of a questionnaire. Next, the collected data was processed using the Paired T-test statistical test with a significance level (α) of 0.00. The research results showed that there was an increase in respondents' knowledge with a p-value (0.00). The conclusion in this research is that there is an influence between health education on the level of knowledge of female students at SD N 1 Paret, Bolaang Mongondow Regency. It is hoped that the suggestions can become a source of information, knowledge development for respondents, research sites, educational institutions and can be used for research development for future researchers.